2016
DOI: 10.1152/ajpheart.00955.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells preserve neonatal right ventricular function in a porcine model of pressure overload

Abstract: (MSCs) have not been evaluated in a preclinical model of pressure overload, which simulates the pathophysiology relevant to many forms of CHD. A neonatal swine model of RV pressure overload was utilized to test the hypothesis that MSCs preserve RV function and attenuate ventricular remodeling. Immunosuppressed Yorkshire swine underwent pulmonary artery banding to induce RV dysfunction. After 30 min, human MSCs (1 million cells, n ϭ 5) or placebo (n ϭ 5) were injected intramyocardially into the RV free wall. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 43 publications
(49 reference statements)
3
44
0
4
Order By: Relevance
“…We previously showed that a different stem cell type, bone marrow-derived mesenchymal stem cells (MSCs), preserved right ventricular (RV) size and function in a neonatal swine model of RV pressure overload at 4 weeks after intramyocardial injection [4]. At the time of this initial study, a contemporaneous cohort of animals underwent RV injection with c-kit þ CPCs but had not yet been analyzed.…”
mentioning
confidence: 99%
“…We previously showed that a different stem cell type, bone marrow-derived mesenchymal stem cells (MSCs), preserved right ventricular (RV) size and function in a neonatal swine model of RV pressure overload at 4 weeks after intramyocardial injection [4]. At the time of this initial study, a contemporaneous cohort of animals underwent RV injection with c-kit þ CPCs but had not yet been analyzed.…”
mentioning
confidence: 99%
“…These investigators found improvement in RV parameters after 30 days; however, they identified relatively few hMSCs retained in the myocardium at day 28 [26]. It is plausible that our findings differ based on the age (neonatal vs. adult) and disease state (none vs. PH with RV remodeling) of the animals studied; the dose of cells administered and route of injection, and the use of immune suppression, which our study did not use.…”
Section: Discussionmentioning
confidence: 58%
“…In 2011, it was demonstrated that intramyocardially injected BM-derived c-kit + cells stimulate endogenous cardiogenic progenitors without evidence for transdifferentiation or fusion of cells [353]. This was further confirmed in several other studies showing the increase of c-kit + CSC within the heart tissue after MSC transplantation [354,355]. Recently, the injection of BM-derived MNC conditioned media alone was found to significantly increase the number of circulating Sca-1 + and c-kit + cells and favors the infiltration of beneficial endogenous BMderived cells, indicating paracrine signaling as the prevailing mechanism of resident cell recruitment [356].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 83%
“…The amount of proliferating cardiomyocytes and endothelial cells was significantly elevated after MSC transplantation [354]. As these proliferating cells failed to co-express the active fragment of the Notch 1 receptor N1ICD, the authors concluded that proliferating cells did not arise from endogenous CSCs [354,357].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%